Top level cooperative leaders conference on enhancing cooperative capability ; Report and papers - Japan , Tokyo (New Delhi, 1984)
The Conference was attended by both representatives of go vernments comprising, Ministers/Heads of Departments con cerned with cooperative development from several countries in Asia and Africa as well as the non-official leaders of the co operative movements which were members of the ICA from Asia. This collaborative effort of the AARRO and the ICA provided a useful forum for the exchange of wide and varying experiences and for the drawing up of guidelines for enhancing cooperative capability. The discussions centred round 7 papers presented under three main heads: (i) Cooperative Development; (ii) Coopera tives and the Poor; and (iii) Integrated Rural Development.
Keywords: Cooperation